Participatory Leadership and Motivation Boost Rural Community Productivity: Kepemimpinan Partisipatif dan Motivasi Mendorong Produktivitas Masyarakat Pedesaan - Sitanggang, Dora Iccabella; Rizky, Muhammad Chaerul; Gulo, Tri Nofita; Simanjuntak, Yunita; Zendrato, Aprilia (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Productivity in rural communities, especially those reliant on agriculture and small businesses, is often influenced by leadership dynamics and community motivation. Specific Background: In Desa Ronggurnihuta, Kabupaten Samosir, a rural area characterized by traditional livelihoods, the role of local leaders and motivational factors remains underexplored, presenting a critical gap in rural development studies. Knowledge Gap: While previous research has focused on macroeconomic and policy interventions, limited studies have addressed the micro-level interactions between leadership style, motivation, and community productivity in rural Indonesian settings. Aims: This study aims to examine how participative leadership and motivational strategies contribute to enhancing community productivity in Desa Ronggurnihuta. Results: The study, employing a qualitative descriptive approach through interviews, observations, and document analysis, finds that participative leadership—characterized by active community involvement—and motivation via socio-economic incentives significantly boost productivity in farming and small-scale enterprises. Novelty: The findings highlight the nuanced interplay between participative leadership and culturally embedded motivation, offering a micro-perspective often overlooked in rural development research. Implications: The study suggests that empowering local leadership and implementing context-specific motivational frameworks are essential for sustainable community development in rural Indonesian settings. Highlights: Participative leadership fosters engagement in rural communities. Motivation through social and economic rewards boosts productivity. Local leadership is essential for sustainable rural development. Keywords: Leadership, Motivation, Productivity, Village Community